Restoring @bajuyuli Business Image on Instagram Social Media in Facing the Threat of Cyber Crime Phishing - Zianisya, Salwa Rahma; Rosyidudin, Eki; Khotimah, Ima Khusnul; Nurfalah, Farida; Wihayati, Welly (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research has a background regarding phishing and business image. This study aims to find out the recovery of business image by the @bajuyuli team and to find out the efforts to prevent cyber crime phishing by the @bajuyuli team. This research uses qualitative data analysis methods and techniques. The technique for determining informants in this study uses the purposive sampling technique. The purposive sampling technique is a method of selecting samples based on the desired goal by the researcher. With this technique, the researcher used three informants consisting of, @bajuyuli business owners, Instagram @bajuyuli admins, and customer @bajuyuli. The results of the research emphasized the importance of transparency, data security, and the role of Public Relations in overcoming crises and strengthening business reputations in the digital world. Efforts to combat such attacks require quick and effective recovery measures, as well as increased cybersecurity awareness among business owners and teams. This research provides insight into the importance of protecting business image from cyber attacks.